The role of foreign venture capital and foreign business angels in start-ups' early internationalization: The case of Polish ICT start-ups - Krystian Bigos; Adam Michalik (Entrepreneurial Business and Economics Review (EBER), 2023)
Objective: The objective of the article is to examine the role of foreign venture capital and foreign business angels in companies' early internationalization based on the example of Polish ICT start-ups. Research Design & Methods: We based the scientific argument on an analysis of the existing state of knowledge in this area and the empirical research conducted among 220 Polish start-ups, which founded our logistic regression model. Findings: Based on the study, a positive relationship exists between the involvement of foreign venture capital funds in start-ups and their early internationalization. Implications & Recommendations: Start-ups should cooperate with foreign institutions, such as venture capital funds, as their knowledge and experience can be a source of start-ups' early internationalization. We recommend that scholars conduct further in-depth panel studies on the impact of foreign investment funds on the early internationalization process. Contribution & Value Added: The article covers research yet to be undertaken in research analyses in early internationalization and can serve as a starting point for further in-depth studies of the phenomenon, also based on start-ups from other countries.
Keywords: F23; G24; L26; 330; venture capital; business angel; early internationalization; international entrepreneurship; financial capital